Interactions between the invasive barnacle Balanus glandula and indigenous barnacles along the South African coast : the role of temperature and the implications of climate change - Pope, Haley Renee (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.